A preliminary study on the quality of locally-produced synthetic resin teeth in terms of blanching and distortion, craze resistance, and color stability - Largoza, Ma. Nyra T.
Until now, there has been no recognized body which conducts tests to verify the quality of locally manufactured acrylic resin teeth. In this study, three different brands were tested. Four sets of upper anterior teeth of four different shades for each brand were subjected to the following: Blanching & Distortion Test, Craze Resistance Test, & Color Stability Test. One foreign, A.D.A. - approved brand was included in the testing as a basis for comparison. One half of the sample set were exposed, their contralaterals acted as controls. Results showed that all three local brands passed all three tests.